1995
DOI: 10.1111/j.1526-100x.1995.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

The Establishment and Maintenance of a Species‐Rich Grassland on a Reclaimed Opencast Coal Site

Abstract: We conducted an experiment with the dual aims of (1) examining the feasibility of establishing a species‐rich grassland using a commercially available grass and wild‐flower seed mixture and (2) examining the effects of different defoliation and fertilizer managements on the productivity, species richness, diversity, and composition of a species‐rich grassland established on a site reclaimed after opencast coal mining. The use of the seed mixture successfully established a sward of some 18–25 species per square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Species that invade mine lands are often those with effective seed dispersal mechanisms, high seed production rates, local availability, and tolerance of mine soil conditions (Ashby 1984). Seed sources for Cirsium arvense , Sonchus arvensis , Taraxacum officinale , and Tussilago farfara on revegetated opencast coal sites have been attributed to wind dispersal (Chapman & Younger 1995). Spreading of hay on the surface of red mud was practiced on the BRDA as a method for dust suppression until 2001 and may have provided the seed source for much of the established species on the BRDA.…”
Section: Discussionmentioning
confidence: 99%
“…Species that invade mine lands are often those with effective seed dispersal mechanisms, high seed production rates, local availability, and tolerance of mine soil conditions (Ashby 1984). Seed sources for Cirsium arvense , Sonchus arvensis , Taraxacum officinale , and Tussilago farfara on revegetated opencast coal sites have been attributed to wind dispersal (Chapman & Younger 1995). Spreading of hay on the surface of red mud was practiced on the BRDA as a method for dust suppression until 2001 and may have provided the seed source for much of the established species on the BRDA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, manual seed collection is extremely time consuming (Stevenson et al 1995), whereas seed harvesting with vacuum machines has a limited effectiveness and damages the vegetation and the invertebrate communities of the donor site (Stevenson et al 1997). Commercial seed mixtures also lack many of the target species and their ecotypes (Lippitt et al 1994; Chapman & Younger 1995). In contrast, cattle dung sowing has certain advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it might be appropriate to allow one year for turves, whether whole or rotovated, to settle down and become established without grazing or cutting, followed in subsequent years by a July cut with removal of biomass and a second cut in September, or light grazing with cattle where possible. A study comparing cutting and grazing as maintenance regimes on a species‐rich grassland site established on a restored opencast coal site in the north of England ( Chapman & Younger 1995) showed that cutting maintained species richness better than grazing.…”
Section: Discussionmentioning
confidence: 99%